Biometria ocular ultrassonográfica e dopplerfluxometria das artérias oftálmica interna e central da retina em macaco-prego (Sapajus spp) - Rodas, Natália Rodrigues [UNESP] (2014)
This study aimed to evaluate the ocular biometric variables using ocular ultrasound A mode and B mode and dopplerfluxometry of the the internal ophthalmic and central retinal arteries. Were evaluated 18 animals (36 eyes) of capuchin monkeys in captivity, 10 females and 8 males, clinically healthy. Measurements of the anterior chamber (D1), lens thickness (D2), vitreous chamber (D3) and axial length of the eyeball (D4) were performed, as well as the dopplerfluxometry of the internal ophthalmic and central retinal arteries, represented by peak systolic velocity (PSV), end diastolic velocity (EDV), resistivity index (RI) and pulsatility index (PI). The biometric measurements averages found in ocular ultrasonography B mode and A mode were : B mode: D1= 2,79 ± 0,19; D2= 3,25 ± 0,22; D3= 10,17 ± 0,48; D4=16,23 ± 0,50; A mode: D1= 2,16 ± 0,16; D2=3,12 ± 0,14; D3=11,12 ± 0,27; D4= 16,38 ± 0,34. In the dopplerfluxometry of the internal ophthalmic, average values of the variables obtained were: RI=0,71± 0,03; PI=1,30 ± 0,15; PSV=36,89 ± 10,57; EDV=10,52 ± 3,21; and the central retina artery were: RI=0,56 ± 0,04; PI=0,81 ± 0,09; PSV= 21,47 ± 7,23; EDV= 9,95 ± 3,31. Reference values obtained may aid in the diagnosis of eye diseases in capuchin monkeys, and may be used in future studies with this species